Efek Akut Manuver Slow Deep Breathing terhadap Penderita Hipertensi Esensial Derajat 1 dan 2 - Wendy Wiharja; Raymond Pranata; Abraham Fatah; Bertha Bertha; Ivani C Kurniadi; Hadrian Deka; Vito A Damay (Jurnal Kardiologi Indonesia, 2016)
Background: Hypertension remains one of the most common health issues in Indonesia. Slow deep breathing maneuver is a non-pharmacological therapy that achieves systolic and diastolic blood pressure lowering effect through sympathetic and parasymphathetic firing rate.Methods: This study was done using cross-sectional design, with consecutive sampling. Sample population was patients with hypertension stage 1 and 2, age range 40-55 years old, who came to Puskesmas Balaraja.Results: Systolic blood pressure lowered from 148.04+5.82 mmHg to 138.15+5.9 mmHg (p<0.05) and diastolic pressure lowered from 85+5.05 mmHg to 78.47+5.46 mmHg (p<0.05). This study showed that there is a relation between the manuever and lowering the systolic and diastolic blood pressure (p=0.000, on T-Test analytical study).Conclusion: Based on the data, the slow deep maneuver can be used as a non-pharmacological therapy for patients with hypertension. Because the effect is acute, it can be considered for hypertension crisis, but further studies are still needed.